2022
DOI: 10.5435/jaaos-d-22-00525
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surgeon and Hospital Volume on Total Hip Arthroplasty Patient-Reported Outcome Measures: An American Joint Replacement Registry Study

Abstract: Background:Some studies have shown lower morbidity and mortality rates with increased surgeon and hospital volumes after total hip arthroplasty (THA). This study sought to determine the relationship between surgeon and hospital volumes and patient-reported outcome measures after THA using American Joint Replacement Registry data.Methods:Using American Joint Replacement Registry data from 2012 to 2020, 4,447 primary, elective THAs with both preoperative and 1-year postoperative Hip Dysfunction and Osteoarthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Major complications were lower in THA patients but not in TKA patients. Oakley et al [ 16 ] utilized the American Joint Replacement Registry and defined low-volume (1 to 42), medium-volume (42 to 96), and high-volume (≥96) surgeons and low-volume (1 to 201), medium-volume (201 to 392), and high-volume (≥392) hospitals for THA. These authors did not find higher surgeon or hospital volume to correlate with higher patient-reported outcome scores following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Major complications were lower in THA patients but not in TKA patients. Oakley et al [ 16 ] utilized the American Joint Replacement Registry and defined low-volume (1 to 42), medium-volume (42 to 96), and high-volume (≥96) surgeons and low-volume (1 to 201), medium-volume (201 to 392), and high-volume (≥392) hospitals for THA. These authors did not find higher surgeon or hospital volume to correlate with higher patient-reported outcome scores following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that higher volume is linked to better patient-reported outcomes for procedures such as total knee arthroplasty and lumbar spine fusion, but not for total hip arthroplasty. 11,17,24 To the best of our knowledge, this is the first study to investigate the relationship between surgeon volume and patient-reported outcomes in primary ACLR. Clinic volume was assessed in a recently published study from the Norwegian Knee Ligament Registry, where the authors found an increased improvement in 5-year KOOS QoL and a decreased rate of TFs (defined as QoL \44) among patients operated on at clinics with higher ACLR volume.…”
Section: Subjective Knee Functionmentioning
confidence: 99%